Active eosinophils regulate host defence and immune responses in colitis - Gurtner, Alessandra; Borrelli, Costanza; Gonzalez-Perez, Ignacio; Bach, Karsten; Acar, Ilhan E.; Núñez, Nicolás G.; Crepaz, Daniel; Handler, Kristina; Vu, Vivian P.; Lafzi, Atefeh; Stirm, Kristin; Raju, Deeksha; et al. (Nature (London), 2023)
In the past decade, single-cell transcriptomics has helped to uncover new cell types and states and led to the construction of a cellular compendium of health and disease. Despite this progress, some difficult-to-sequence cells remain absent from tissue atlases. Eosinophils—elusive granulocytes that are implicated in a plethora of human pathologies 1 – 5 —are among these uncharted cell types. The heterogeneity of eosinophils and the gene programs that underpin their pleiotropic functions remain poorly understood. Here we provide a comprehensive single-cell transcriptomic profiling of mouse eosinophils. We identify an active and a basal population of intestinal eosinophils, which differ in their transcriptome, surface proteome and spatial localization. By means of a genome-wide CRISPR inhibition screen and functional assays, we reveal a mechanism by which interleukin-33 (IL-33) and interferon-γ (IFNγ) induce the accumulation of active eosinophils in the inflamed colon. Active eosinophils are endowed with bactericidal and T cell regulatory activity, and express the co-stimulatory molecules CD80 and PD-L1. Notably, active eosinophils are enriched in the lamina propria of a small cohort of patients with inflammatory bowel disease, and are closely associated with CD4 + T cells. Our findings provide insights into the biology of eosinophils and highlight the crucial contribution of this cell type to intestinal homeostasis, immune regulation and host defence. Furthermore, we lay a framework for the characterization of eosinophils in human gastrointestinal diseases. Single-cell transcriptomic profiling and functional assays are used to identify subpopulations of eosinophils that are present in the mouse gastrointestinal tract and provide insight into the role of these cells in inflammatory bowel diseases in humans.